Solar Atlas of New Zealand from satellite imagery. Issue 4 (1st October 2020) - Brent, Alan C.; Hinkley, James (Jim); Burmester, Daniel; Rayudu, Ramesh
ABSTRACT: The utilisation of solar resources has become of utmost importance for the transition of the global, carbon intensive economy. In New Zealand the uptake of solar energy has increased substantially, but the relative contribution to the overall energy mix is still small. Previous research efforts on the solar resource across the country are revisited with improved satellite-modelled data from Solargis to derive a solar atlas for the country. A comparison is made with NIWA data, which shows that the modelled data are at an adequate level of accuracy and improves our understanding of the solar resource at an appropriate spatial and temporal resolution. The solar atlas makes available a commercial satellite data source and informs further investigations into how solar can, and will, play a more meaningful role in our transition to a low carbon future.